STUDY ON MORPHOLOGICAL AND BIOLOGICAL CHARACTERISTICS OF OENOPIA KIRBYI (COLEOPTERA: COCCINELLIDAE) IN DA LAT CITY, LAM DONG, VIETNAM - Nguyen Thanh Thuy Tien; Nguyen Duc Sang; Le Thi Thanh Thuy; Nguyen Thi Thu Hue; Nguyen Thi Thuy Ngan; Tran Thi Thu Dan (Tạp chí Khoa học Đại học Đà Lạt)
Ladybirds are natural enemies of many agricultural crop pests, such as aphids, scale insects, mealybugs, whiteflies, and thrips. This paper focuses on the morphological and biological characteristics of Oenopia kirbyi (Coleoptera: Coccinellidae) in Da Lat city (Lam Dong province). Field-collected adults of Oenopia kirbyi were reared in plastic boxes under laboratory conditions and fed on aphids. The egg phase lasted 4.45 ± 0.71 days; the four larval stages lasted 2.63 ± 0.52 days, 1.91 ± 0.73 days, 1.70 ± 0.46 days, and 5.78 ± 0.95 days, respectively; and pupae lasted 7.02 ± 0.91 days. The total duration of the immature stages was 23.49 days. The adult longevity of males and females was 67.13 ± 18.77 days and 82.83 ± 20.25 days, respectively. The fecundity was 414.00 ± 131.33 eggs on average. The rate of hatched eggs, emerged adults, and the female/male ratio were 80.85%, 96.53%, and 1.78, respectively. These results provide basic data for rearing Oenopia kirbyi for use as a biological control of crop pests.